Women's Shelters and Municipalities in Turkey : Between Solidarity and Benevolence - Berna Ekal (EchoGéo)
Women's shelters, the product of second wave feminisms all over the world, are both a tool for solidarity with women who face violence and a way of doing feminist politics based on women's experiences of violence and solidarity. Accordingly, most academic works on women's shelters focus on these dimensions of feminist shelters. Based on ethnographic work in shelters in Turkey and by dwelling upon the literature of the anthropology of the state, this article, on the other hand, argues that in the case of Turkey, women's shelters are to be treated as bureaucratic institutions, not as feminist structures, as most of the shelters are embedded in the administrative structure of municipalities and central state's social services.